Evolução da área florestada na região de Botucatu/SP no período de 1996 a 2008 visando à implantação da Reserva Legal - Cataneo, Pedro Fernando; Bueno, Osmar de Carvalho [UNESP] (EIA Energy in Agriculture, 2010)
Due to the considerations on the Legal Forest Reserve, the aim of this paper is to show the distribution of the farming areas in the region and their application – especially natural forests. Also, to compare the municipal values with those stated in the Brazilian Forest Code in order to analyze the process of implementing 20% of forest area in relation to the total farming area, at municipal and regional levels, not considering the areas of each of the farms nor the watershed to which they belong with the Brazilian Forestry Code. The work results show that all municipalities in the region of Botucatu do not have forest areas equal or greater than 20% of total area. Therefore, a non-exploratory reforestation procedure will have to be implemented to follow legal requirements. Finally, the results show that the city of Areiópolis will face the greatest difficulties in implementing the 20% of forests with regard to the Legal Forest Reserve, until 2021, when the deadline stated by the Legal Code expires. According to the same variables, the municipalities of Anhembi, Conchas, Laranjal Paulista, Pereiras, Pratânia and São Manuel will face medium-level difficulties, whereas Bofete, Botucatu, Itatinga and Pardinho will implement it the easiest way.

Devido às atuais discussões sobre a Reserva Legal, este trabalho tem por objetivo conhecer a distribuição das áreas agrícolas da região de Botucatu, em suas variadas explorações, com especial ênfase às áreas de mata natural, comparar os valores municipais com aqueles dispostos no Código Florestal Brasileiro, de forma a analisar o processo de implantação dos 20% de área de florestas em relação à área total agrícola, em nível macro municipal e regional, sem considerar as áreas de cada uma das propriedades agrícolas e nem a bacia hidrográfica às quais pertencem, conforme consta no Código Florestal Brasileiro. Os resultados do trabalho mostram que todos os municípios pertencentes à região não possuem áreas de mata natural superiores a 20% e que terão que reflorestar sem finalidade exploratória, a não ser cumprir os preceitos da legislação. Para a implantação de florestas para compor o percentual de 20% de Reserva Legal, em nível macro, até o ano de 2021, quando termina o prazo disposto no Código Legal, Bofete, Botucatu¸ Itatinga e Pardinho encontrarão as menores dificuldades, Anhembi, Conchas, Laranjal Paulista, Pereiras, Pratânia e São Manuel terão dificuldades médias, enquanto que Areiópolis encontrará a maior dificuldade.
Enlargement of the forested area in the region of Botucatu, Brazil, from 1996 to 2008, aiming at the implementation of a legal forest reserve
Keywords: Reforestation Indexes; Reforestation; Brazilian forestry code; Índices de reflorestamento; Reflorestamento; Código Florestal